Exposure and Health Risks Posed by Potentially Toxic Elements in Soils of Metal Fabrication Workshops in Mbarara City, Uganda - Nuwamanya, Eunice; Byamugisha, Denis; Nakiguli, Caroline K.; Angiro, Christopher; Khanakwa, Alice V.; Omara, Timothy; Ocakacon, Simon; Onen, Patrick; Omoding, Daniel; Opio, Boniface; Nimusiima, Daniel; Ntambi, Emmanuel (My University, 2024)
Metal fabrication workshops (MFWs) are common businesses in Ugandan cities, and especially those producing metallic security gates, window and door frames (burglar-proof), and balcony and staircase rails. The objective of this study was to comparatively assess the pollution levels and potential health risks of manganese (Mn), chromium (Cr), cadmium (Cd), lead (Pd) and nickel (Ni) in pooled surface soil samples from four 5-, 7-, 8-, and 10-year-old MFWs (n = 28) and a control site(n=8) in Mbarara City, Uganda. The concentration of the potentially toxic elements(PTEs) was determined using inductively coupled plasma–optical emission spectrometry. Contamination, ecological, and human health risk assessment. Indices and models were used to identify any risks that the PTEs could pose to the pristine environment and humans. Our results showed that PTE pollution of soils is occurring in the MFWs than at the control site. The mean concentrations of the PTEs (mg kg−1) in the samples were: Mn (2012.75±0.23–3377.14±0.31), Cr (237.55±0.29–424.93±0.31), Cd (0.73±0.13–1.29±0.02), Pb (107.80±0.23–262.01±0.19), and Ni (74.85±0.25–211.37±0.14). These results indicate that the PTEs could plausibly derive from the fabrication activities in these workshops, which is supported by the high values of contamination factors, index of geo-accumulation, and the overall increase in pollution load indices with the number of years of operation of the MFWs. Human health risk assessment showed that there are non-carcinogenic health risks that could be experienced by children who ingest PTEs in the soils from the 7-, 8- and 10-year-old MFWs. The incremental life cancer risk assessment suggested that there are potential cancerous health effects of Cd and Ni that could be experienced in children (who ingest soils from all the four MFWs) and adults (ingesting soils from the 8- and 10-year-old MFWs). This study underscores the need to implement regulatory guidelines on the operation and location of MFWs in Uganda. Further research should be undertaken to investigate the emission of the PTEs during welding operations in the MFWs.
Keywords: Metal fabrication workshops; Toxic metals; Health risks; Soil pollution; Average daily doses; Carcinogenic risk; Hazard index